2006
DOI: 10.1080/00365540600585073
|View full text |Cite
|
Sign up to set email alerts
|

Tick-borne encephalitis in eastern France

Abstract: Each y a few cases of TBE infection are described in Alsace, France which lies at the occidental limit of the endemic zone of tick-borne encephalitis (TBE). Hence we carried out a retrospective epidemiological and clinical study of TBE infection in Alsace. Data were collected from serological results sent to the Institut de Virologie (Université Louis Pasteur) in Strasbourg. All samples positive for specific IgM against TBE were retained. The physician in charge of each patient was asked to provide clinical, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 16 publications
1
14
1
Order By: Relevance
“…The TBEV seroprevalence observed in our study is similar to that reported by previous French studies conducted among participants in contact with the forest [48]. This seroprevalence is consistent with the low and stable number of cases of human clinical TBE diagnosed in France (an average of about ten cases per year from 1968 to 2003), especially confined to eastern France (essentially Alsace, Lorraine, Franche-Comt e) and the low prevalence in I. ricinus, which varies from 0.1% to 5% in European areas where TBEV is endemic [9,49]. The incidence of TBE in France is lower than that observed in neighbouring countries such as Germany (0.3 to 0.7 cases per 100 000) or Switzerland (1.5 to 3.3 cases per 100 000), whereas the greatest number of clinical cases is reported in the Czech Republic, Baltic States and Slovenia (incidence exceeding 10 cases per 100 000 inhabitants depending on the year) [50].…”
Section: Discussionsupporting
confidence: 72%
“…The TBEV seroprevalence observed in our study is similar to that reported by previous French studies conducted among participants in contact with the forest [48]. This seroprevalence is consistent with the low and stable number of cases of human clinical TBE diagnosed in France (an average of about ten cases per year from 1968 to 2003), especially confined to eastern France (essentially Alsace, Lorraine, Franche-Comt e) and the low prevalence in I. ricinus, which varies from 0.1% to 5% in European areas where TBEV is endemic [9,49]. The incidence of TBE in France is lower than that observed in neighbouring countries such as Germany (0.3 to 0.7 cases per 100 000) or Switzerland (1.5 to 3.3 cases per 100 000), whereas the greatest number of clinical cases is reported in the Czech Republic, Baltic States and Slovenia (incidence exceeding 10 cases per 100 000 inhabitants depending on the year) [50].…”
Section: Discussionsupporting
confidence: 72%
“…However, the occurrence of WNV autochthonous infection in France is rare and TOSV is more often responsible for meningitis than for encephalitis. For TBE there is no active surveillance because the number of TBE cases is expected to be low in France (between 5 and 10 cases per year) and its occurrence is generally limited to the eastern region (Alsace) which is the occidental limit of the European endemic zone [28]. Three cases of TBE, one of TOSV and one of WNV encephalitis were reported in the prospective study.…”
Section: Discussionmentioning
confidence: 99%
“…The study focussed on a 4.0-hectare area at Murbach (47°55’03N, 07°08’46E; average altitude of 630 m) in Guebwiller Valley, Alsace, which is the region where most of the human cases of TBEV have been reported in the last two decades [ 37 ] and where the virus was isolated from questing ticks in 2010 (unpublished data). The site is covered by mixed forests classified as Asperulo-Fagetum beech forests, with a predominance of Fagus sylvatica beech and Abies alba European silver fir.…”
Section: Methodsmentioning
confidence: 99%
“…France is located on the western border of the known distribution of TBEV, with about ten cases reported each year since the discovery of TBEV in 1968. Most human clinical cases of TBE have been reported in Alsace, a region in the extreme east of France, bordering Germany and Switzerland [ 37 , 38 ]. Contrary to the endemic area of TBEV in these neighbouring countries, the incidence in Alsace is low, with a yearly incidence of 0.5/100,000 inhabitants on average.…”
Section: Introductionmentioning
confidence: 99%